2023
DOI: 10.1371/journal.pone.0280687
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative overweight and obesity do not cause inferior outcomes following open-wedge high tibial osteotomy: A retrospective cohort study of 123 patients

Abstract: Open-wedge high tibial osteotomy (OWHTO) is effective in treating medial compartment osteoarthritis. The association between body mass index (BMI) and outcomes following OWHTO is being debated. This study compared radiographic and clinical outcomes between patients with preoperative overweight, obesity, and normal BMI following OWHTO for medial compartment osteoarthritis. In total, 123 patients (123 knees) who underwent OWHTO for medial compartment osteoarthritis were enrolled and were divided into normal-BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Therefore, no correlation was determined between BMI and the development of complications or conversion to TKA. Similarly, in a study with a 2-year follow-up, Wu et al [17] reported that there was no correlation between BMI values and conversion to TKA, the development of complications, or clinical, functional, and radiological healing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, no correlation was determined between BMI and the development of complications or conversion to TKA. Similarly, in a study with a 2-year follow-up, Wu et al [17] reported that there was no correlation between BMI values and conversion to TKA, the development of complications, or clinical, functional, and radiological healing.…”
Section: Discussionmentioning
confidence: 99%
“…While SBTKA surgery is still a matter of debate among orthopedists, there are serious concerns about performing SBTKA to O and MO patients. Obesity is a strong risk factor for bilateral osteoarthritis of the knees [6][7][8]. Close to 40% of the world population and 900 million people worldwide are obese, and the numbers increase daily.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial fat necrosis and WHP are common in MO patients [ 5 ]. Due to the negative effects of obesity on the immune system and decreased subcutaneous tissue oxygenation, the rate of infection development in these patients is quite high, which increases the probability of a prosthesis infection [ 5 , 6 ]. It should not be forgotten that SBTKA has advantages such as high patient satisfaction, short general rehabilitation period and low cost.…”
Section: Introductionmentioning
confidence: 99%